Ograniczenie konstytucyjnych wolności i praw osobistych w czasie trwania stanów nadzwyczajnych - Jabłoński, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The fundamental issue raised in this elaboration comes down to an attempt at identifying the character and content of constitutional guarantees of freedom and individual rights during extraordinary measures martial law, state of emergency and natural disaster. Three essentials in immanent connection are raised in this respect: constitutional conception of freedom and personal rights, principles and values legalizing the limitations in constitutional guarantees of freedom and individual rights and particular constitutional guarantees excluding the ability of constricting some specific liberties and rights during extraordinary measures. The intention of this analysis is to establish whether the existing solutions at the level of RP Constitution arrangements indeed ensure the system not being edited in terms of the particular category of freedom and individual rights in Polish legal order.
Keywords: freedoms and personal rights; Constitution of Poland 1997; limitation of constitutional freedoms; extraordinary measures